To Determination of Heating Speed of Surface Element of Module Industrial Furnace Recuperator of High-Temperature Heat Technologies at Engineering and Automotive and Tractor Plants - V. V. Shidlovsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains an analysis of thermal stressed state of a cast-iron recuperator element wall in the case when a cast-iron needle recuperator operates in the state of  elasticity and elastic-plasticity.Heating speed evaluation of  heat-exchange surface at furnace start-up is given in the paper.